2008
DOI: 10.2337/db07-0558
|View full text |Cite
|
Sign up to set email alerts
|

AHSG Tag Single Nucleotide Polymorphisms Associate With Type 2 Diabetes and Dyslipidemia

Abstract: OBJECTIVE-The gene encoding the ␣2 Heremans-Schmid glycoprotein (AHSG) is a credible biological and positional candidate gene for type 2 diabetes and the metabolic syndrome, and previous attempts to relate AHSG variation with type 2 diabetes and obesity in Swedish and French Caucasians have been largely successful. We related seven frequent AHSG tag single nucleotide polymorphisms to a range of metabolic traits, including type 2 diabetes, obesity, and dyslipidemia. RESEARCH DESIGN AND METHODS-The polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 28 publications
4
42
2
Order By: Relevance
“…Additionally fetuin-null mice have been protected to weight gain when they have been challenging with a high-fat diet 14,21 . Furthermore in those animal model lower serum free fatty acid and triglyceride levels have been observed 15,22 . Mathews et al, based on mice study, suggested that the absence of fetuin-A may contribute to the improvement of insulin sensitivity associated with aging 23 .…”
Section: The Relationship Between Fetuin-a and Insulin Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…Additionally fetuin-null mice have been protected to weight gain when they have been challenging with a high-fat diet 14,21 . Furthermore in those animal model lower serum free fatty acid and triglyceride levels have been observed 15,22 . Mathews et al, based on mice study, suggested that the absence of fetuin-A may contribute to the improvement of insulin sensitivity associated with aging 23 .…”
Section: The Relationship Between Fetuin-a and Insulin Resistancementioning
confidence: 99%
“…Moreover the role of fetuin-A gene variations in regulation of lipolysis and lipid disturbances have been postulated, for instance two fetuin-A SNPs (-469T>G and IVS6+98C>T) were connected to dyslipidemia and -469T>G SNP which is located in the 5' region of fetuin-A gene was associated with insulin-mediated inhibition of lipolysis and stimulation of lipogenesis. What is more, three fetuin-A gene SNPs (-843A>T, -469T>G and 6670T>C) have been linked to circulating levels of cholesterol 15,30 . Furthermore, fetuin-A knockout mice have a lower triglyceride and free fatty acid level as compared with wild-type controls 7 .…”
Section: Fetuin-a and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…SNP rs11926347, in an intron of ABCC5 (OMIM 60521), and SNP rs6795506, near the 5' end of AHSG (OMIM 138680), had extremely small p-values (Table 8). Among the other nine genes, ADIPOQ (OMIM 605441, 612556) has been widely reported to be associated with obesity and diabetes [21-24]; FNDC3B (OMIM 611909) is involved in positive regulation of adipogenesis [25]; and DGKG (OMIM 601854) and AHSG (OMIM 138680) have been reported to be associated with obesity-related metabolic traits [26,27]. The remaining genes have no reported relation to obesity-related metabolic traits based on our literature review.…”
Section: Resultsmentioning
confidence: 99%